Economic interventions to ameliorate the impact of COVID-19 on the economy and health: an international comparison - Danielli,S; Patria,R; Donnelly,P; Ashrafian,H; Darzi,A (Journal of Public Health, 2021)
BackgroundThe COVID-19 pandemic continues to challenge governments and policymakers worldwide. They have rightfully prioritised reducing the spread of the virus through social distancing interventions. However, shuttered business and widespread restrictions on travel and mobility have led to an economic collapse with increasing uncertainty of how quickly recovery will be achieved.MethodsThe authors carried out a review of publicly available information on the economic intervention’s countries have put in place to ameliorate the impact of COVID-19.ResultsThe strategies and scale of economic interventions have been broad, ranging from 2.5% to a reported 50% of Gross Domestic Product.ConclusionsNumerous countries are beginning to ease lockdown restrictions and restart economies in different ways. There is therefore evolving, real-world data that should be used dynamically by governments and policymakers. The strategies on restarting the economy must be balanced against the uncertainty of a possible second wave of COVID-19. A nuanced approach to easing restrictions needs to take into account not only immediate risk to life but longer-term risks of widening inequalities and falling life expectancy.